BRACHIOPODS OF THE FAMILY LICHAREWIIDAE IN NORTHEASTERN RUSSIA - Solomina R.V. (My University, 2001)
Abstract-Licharewia-Yike brachiopods from northeastern Russia are studied. Their generic diagnoses are emended and their species composition and stratigraphie range are revised. Two new genera Neotumarinia and Labuella are described.